PENGARUH BENTUK TES FORMATIF DAN SIKAP BELAJAR TERHADAP HASIL BELAJAR MEMBACA BAHASA ARAB - Hitu, Jehan Ananda Aliyah Kapitan; Isnaini, Muhammad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
This research aims to investigate the effect of formative tests and students 'attitudes toward students' reading comprehension at Madrasah Aliyah Negeri (MAN) 13 Jakarta. The method employed in this research is true experiment. The results showed that: (1) the result of students' reading comprehension who were given the formative test in narrative form is higher than the group of students who were given the multiple choice of formative test, (2) there is an positive interaction between the formative test and the students' attitude toward the students' reading comprehension, (3) the average reading scores of students who have positive attitude toward Arabic subject is higher when they do the narrative form of formative test, (4) the average reading scores of students who were given the formative test in narrative form is lower than the students whom were given the multiple choice of formative test despite both group of students have negative attitude toward Arabic subject. The conclusion is that there is an impact of formative tests and students' attitudes toward students' reading comprehension.